Pengaruh Analisa Teknikal Dan Analisa Fundamental Terhadap Pengambilan Keputusan Investasi Produk Emas (Studi Kasus Trader XAUUSD DI PT. Trive Invest Futures) - Muhammad Ibrahim; Robby Irvawan (JAMBIS : Jurnal Administrasi Bisnis, 2025)
Abstract.This study examines technical analysis and fundamental analysis in gold product investment with theaim of determining the effect of technical analysis on gold product investment decision-making, the effectof fundamental analysis on gold product investment decision-making, and the effect of technical analysisand fundamental analysis on gold product investment decision-making for XAUUSD traders at PT. TriveInvest Futures. This study uses a quantitative method of probability sampling with a random samplingtechnique of 100 samples due to a population size of 25,991 people. Based on the results of dataanalysis, it was found that: 1) Technical analysis has a positive and significant effect on investmentdecision-making for gold products for XAUUSD traders at PT. Trive Invest Futures, as evidenced by thet-value (3.831) > t-table (1.984) with a significance level of 1.096. 2) Fundamental analysis has a positiveand significant effect on investment decision making for gold products for XAUUSD traders at PT. TriveInvest Futures, as evidenced by t count (2.168) > t table (1.984) with a significance level of 0.371.3) Technical analysis and fundamental analysis have a positive and significant effect on investmentdecision-making for gold products for XAUUSD traders at PT. Trive Invest Futures, as evidenced by aprobability value of p <0.001, which is less than 0.05, and a calculated t-value of 57.42 > t-table (3.09).The coefficient of determination (R²) is 0.542, indicating that all independent variables of technicalanalysis and fundamental analysis influence investment decision-making by 54.2%. The remaining45.8% is influenced by other variables, referred to as error (e).Keywords: Technical Analysis, Fundamental Analysis, Investment Decisison Making, Goldproducts, XAUUSD Traders